Case Report: Rapid response to gemtuzumab-ozogamicin in a pediatric patient with refractory systemic mastocytosis with AML1::ETO+ acute myeloid leukemia - Song Xue; Man Chen; Hui-Peng Sun; Tong Wang; Li-Na Zhang; Xing-Yu Cao (Frontiers in Immunology)
This article describes a 6-year-old patient diagnosed with “systemic mastocytosis with AML1::ETO+ AML”, he experience refractory disease during the course of treatment and salvage treatment was ineffective. The patient was administered gemtuzumab-ozogamicin therapy, resulting in rapid remission.